Alpha Clique Sdn. Bhd. / Nurul Hidayah Mohd Kamal - Mohd Kamal, Nurul Hidayah (2020)
Alpha Clique Sdn. Bhd. is introducing a new product to the customers which is a towel UV sterilizer with an air purifier known as Smartlux. Nowadays, as many people have lived with a cramped and airless bathroom, thus it will lead to several problems; towels have been used not dry properly and gradually begin to smell. Besides, dust may be attached to the towel which could lead to an allergic reaction. Therefore, the Smartlux can solve these problems without delaying their work. The product will help people with busy lifestyles optimize their time management. So, more work can be done faster. The target market of the product mainly focused in urban areas in Shah Alam. Our main target customer is facility services which need to provide a large amount of towels for their customers. However, they need a short time to dry the towels. Examples of facilities are recreational centers, higher-class hotels, resorts, salons, and fitness centers. Other than that, upscale families are another target market suitable for them who highly value their personal hygiene. The last target market is allergy or asthmatics sufferers. This product will reduce their respiratory problem as it can improve air quality as well as remove the allergen from the air. This product will ease and optimize their time management for people that are busy and have limited time to do household chores. Besides, this product also helps to reduce the usage of electricity and minimize the usage of non-renewable resources. The selling price of the product to sell at the market is RM 382.85.